1985
DOI: 10.1080/01434632.1985.9994214
|View full text |Cite
|
Sign up to set email alerts
|

On the predictive validity of the attitude/motivation test battery

Abstract: Evidence of the predictive validity of composite measures of the 'Attitude/Motivation Test Battery' is provided. The composite measures of Motivation, Integrativeness and Attitude Towards the Learning Situation were correlated with three criterion measures, 'Behavioural Intention' to pursue French study, final French grade, and a global measure of French achievement. The data were collected in six different areas of Canada over a two-year period. The composite measure of Motivation was found to be a better pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
1
16
1
2
Order By: Relevance
“…This support came from two analyses. First, the correlations between students' attitudes and their language achievement were similar to those reported in other studies (e.g., 16: pp. 408-09).…”
Section: Discussionsupporting
confidence: 86%
“…This support came from two analyses. First, the correlations between students' attitudes and their language achievement were similar to those reported in other studies (e.g., 16: pp. 408-09).…”
Section: Discussionsupporting
confidence: 86%
“…Numerous studies have demonstrated associations between scores on these measures and achievement in the L2 (see, e.g., Gardner, 1985). In general, the results indicate that the three components of Motivation tend to be correlated with each other and to correlate more highly with achievement than do the measures of Integrativeness and Attitudes Toward the Learning Situation (Lalonde & Gardner, 1985). These results suggest that motivation plays a primary role in L2 learning, with Integrativeness and Attitudes Toward the Learning Situation playing a supportive role.…”
Section: Attitudes and Motivationmentioning
confidence: 78%
“…These variables can be grouped into five categories: Numerous studies have demonstrated associations between scores on these measures and achievement in the L2 (see, e.g., Gardner, 1985). In general, the results indicate that the three components of Motivation tend to be correlated with each other and to correlate more highly with achievement than do the measures of Integrativeness and Attitudes Toward the Learning Situation (Lalonde & Gardner, 1985). These results suggest that motivation plays a primary role in L2 learning, with Integrativeness and Attitudes Toward the Learning Situation playing a supportive role.…”
Section: Attitudes and Motivationmentioning
confidence: 78%